(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
IT jobs are becoming more and more lucrative and many people are joining the industry. Although numerous scholars have written more about the topic; many have failed to research into the IT industry on how organisational culture and employee job satisfaction can be used as a source of competitive advantage. This study investigates on how the impact of organisational culture on employee job satisfaction can be a source of competitive advantage. Using a case study method, the paper derives quantitative data from the employees of a selected IT Company in India, Head Quarters in Dallas. The selected IT company has four (4) Shared Service Centers in India and Dallas and it is the worst solution providers for few customers. The company has 400 workers working in all the four branches across India.A review of literature in two-fold: (i). Understanding supportive organisational culture and employee job satisfaction and (ii). The impacts of organisational culture on the employee job satisfaction as a source of competitive advantage are conducted. This is followed by a summary of methodology and data analysis, ethical consideration and conceptual framework. Empirical analysis was conducted to determine the effects of organisational culture on employee job satisfaction as a source of competitive advantage. The empirical findings show that cultural traits of communication, motivation, growth opportunities and supervising support in organisations tend to make employees shift mind set and help the firm in its competitive advantage. However, the discussion found out that employees within the company were not motivated enough to perform better due to lack of rewarding culture, growth opportunities (training) culture, communication and supervisory supportive culture.